2020
DOI: 10.1002/ccr3.3044
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of MGRS with immunotactoid glomerulopathy responding to bortezomib, dexamethasone, and rituximab

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Patients present with proteinuria (nephrotic range in more than 60%), and over a half of the patients have hypertension, hematuria, CKD, and hematologic disorders. [ 1 , 6 8 ] The recurrence to allograft was seen in half of the transplanted patients, but usually with a more benign course. [ 5 ] In the largest available series of 73 patients with ITG, Nasr et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients present with proteinuria (nephrotic range in more than 60%), and over a half of the patients have hypertension, hematuria, CKD, and hematologic disorders. [ 1 , 6 8 ] The recurrence to allograft was seen in half of the transplanted patients, but usually with a more benign course. [ 5 ] In the largest available series of 73 patients with ITG, Nasr et al .…”
Section: Discussionmentioning
confidence: 99%
“…In general, successful therapy of an underlying hematologic malignancy may lead to complete remission of (the secondary) ITG [ 19 ], whereas on the other hand specific treatment has been deemed ineffective by others [ 29 ]. In a case of ITG associated with serum monoclonal IgM and a small, insignificant, monoclonal B-cell population Kuang et al [ 30 ] reported, that rituximab alone improved renal function and hypertension, but nephrotic syndrome only could be controlled by additional treatment with bortezomib and dexamethasone. Also, the long-term evolution of the glomerular disease has to be considered since it has been reported that a primarily polyclonal glomerular deposit may transform to a monoclonal pattern [ 31 ] and that there may be monoclonal recurrence of former polyclonal ITG after kidney transplantation [ 15 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%